Impacts of a PECS Instructional Coaching Intervention on Practitioners and Children with Autism. (September 2013) - Ganz, Jennifer B.; Goodwyn, Fara D.; Boles, Margot M.; Hong, Ee Rea; Rispoli, Mandy J.; Lund, Emily M.; Kite, Elizabeth
Abstract There is a growing research literature on the potential benefits of augmentative and alternative communication (AAC) for individuals with autism; however few studies have investigated implementation of AAC within real-life contexts. Thus, the purpose of this study was to investigate the impact of training for practitioners in implementation of aided AAC, and to examine implementation of Picture Exchange Communication System (PECS) in real-life contexts. In particular, this study involved the implementation of instructional coaching to increase opportunities offered by behavioral therapists for their preschool-aged clients to use PECS to make requests. Results indicated increases in therapist implementation of AAC and client use of AAC in trained contexts, with limited generalization to untrained contexts.